PENGUKURAN RUNOUT PADA POROS POMPA VERTIKAL DENGAN MEMVARIASIKAN FEEDING DAN SUDUT PENAMPANG POROS - Zuliantoni, Zuliantoni (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2019)
This study aims to do the machining process, measure runout using dial indicator on vertical pump shaft and examine one-way anova to see the effect of angles shaft circle section on the result of runout measurement on the pump shaft. The shaft of vertical pump was produced by a lathe machine. Calculating values the cutting speed, calculating points the theoretical machining time, and measuring grade the runout using dial indicator at the angle 0o, 90o, 180o, and 270o with 10 points of measurement. The results of measurement of runout are carried out one-way ANOVA to see the effect of angles on average runout value. The results of measurement showed at the points of A, B, C, G, I, and J describing the value of runout exceeds level of permitted tolerance but the runout values at the point D, E, F, and H showed the value accepted because they were in below  of the tolerable allowance. The one-way ANOVA show that the average runout value at four cross section angles of the pump shaft were the same. The value at different pump shaft cross section angles did not show an effect on average runout value produced.